Phytochemical analysis and evaluation of antibacterial activity of various extracts from leaves, stems and roots of Thalictrum foliolosum - Manoj Kumar Mishra (SpringerOpen, 2024)
Abstract Background Thalictrum foliolosum, a member of the Ranunculus family, is recognized for its therapeutic potential in addressing gastric issues, dyspepsia, tooth pain, abdominal colic pain, and piles. The diverse array of secondary metabolites present in the plant contributes to these therapeutic applications. This study aims to uncover and quantify the bioactive secondary metabolites found in the unexplored leaves, stems, and roots of T. foliolosum. Additionally, we also aimed to evaluate the antibacterial activity and MIC values of these extracts against a panel of pathogenic bacteria, such as pathogenic strains, including Escherichia coli, Pseudomonas aeruginosa, Streptococcus mutant and Staphylococcus aureus. Result HPLC analysis suggested all examined compounds were found significantly more in root parts of plant. To determine the potential antimicrobial activity of different plant parts result suggested chloroform fraction of root most effective with variable potency against each examined pathogen at 25-100 µg/ml extracts which indicated rich content of berberine in this fraction. Minimum MIC (121.26 µg/mL) of the chloroform fraction of the root was also supported the results. Fatty acid methyl ester analysis by gas chromatography revealed that the stem contained high levels of fatty acids, such as palmitic acid, stearic acid, and linolenic acid, all of which have antibacterial properties. Conclusion The potential antimicrobial activity of extracts of various plant parts strongly supports the T. foliolosum plant's widespread use in folk medicine for the treatment of various chronic diseases and adulterants with various associated medicinal plant species.